The role of syndromic knowledge in Ethiopian veterinarians’ treatment of cattle - Nyokabi, Ndungu S.; Wood, James L. N.; Gemechu, Gizachew; Berg, Stefan; Mihret, Adane; Lindahl, Johanna F.; Moore, Henrietta L. (Frontiers in Veterinary Science, 2024)
Veterinarians play a significant role in the treatment and prevention of livestock diseases at the farm level, safeguarding public health and ensuring food safety. In sub-Saharan Africa, access to quality veterinary services is a major challenge for livestock farmers due to the low number of publicly employed veterinarians, underfunding and privatisation of veterinary services. Low investment in veterinary services and infrastructure, including a lack of laboratories for diagnosis, has made veterinarians rely on their experience and knowledge of cattle disease symptoms developed over years of practice to diagnose and treat cattle diseases. A cross-sectional survey using a role-play approach was used to collect data on knowledge regarding cattle diseases among veterinarians in veterinary clinics and private practices in Addis Ababa, Oromia and Adama regions in Ethiopia. Veterinarians were given a number of disease scenarios based on “fictive disease symptoms” that are commonly manifested in a sick cow and asked to identify the disease what personal biosecurity they would use, diagnostic tests they would perform, treatments they would prescribe, treatment costs, and additional services and inputs they would recommend to the farmer. The results show that veterinarians could identify endemic cattle diseases through symptoms. The majority of veterinarians did not find it important to report notifiable diseases, a behaviour which could hamper disease surveillance and outbreak response. The advice and services the veterinarians said they would offer and recommend to farmers included improvement in feeding, vaccination, use of artificial insemination, and adoption of farm biosecurity measures that can reduce disease prevalence, and improve food safety, animal health and welfare. Low use of personal protective equipment and other protective biosecurity measures among veterinarians could expose them to zoonotic diseases. The study concludes that there is a need for increased funding for continuous training, improved access to animal health-related information, and investment in infrastructure such as laboratories to enable veterinarians to deliver quality animal health services.